The role of the National Bank of Serbia in regulation of monetary policy - Marjanović Nataša; Prelić Jovan; Belokapić-Čavkunović Jelena (Oditor, 2017)
Monetary stability implies achieving a low and stable inflation rate. Through monetary policy instruments, the central bank seeks to achieve targeted inflation in order to achieve macroeconomic stability. As the main problem in the previous period was high inflation, the NBS has consistently implemented a restrictive monetary policy based on the basic factors of inflation. Its implementation was carried out most often by increasing the reference interest rate and conducting open market operations. For the implementation of inflation targeting policies, sustainable public finances, central bank independence, good forecasting of inflation trends and a good knowledge of the transmission mechanism between monetary policy instruments and inflation should be ensured. The main goal of this paper, based on the current operations of the National Bank of Serbia, is to analyze the success and trends of monetary policy in recent years.